1997
DOI: 10.1007/bf01324806
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation in salivary gland adenocarcinomas with myoepithelial participation

Abstract: We used three markers of cell proliferation mitotic counts, mitotic index and expression of proliferating cell nuclear antigen--to assess the proliferative activity of a series of 78 low-grade salivary adenocarcinomas with myoepithelial participation classified according to: their histological type, the predominant architectural type, and the predominant cytological type. The series included adenoid cystic carcinomas (40), epithelial-myoepithelial carcinomas (19), polymorphous low-grade adenocarcinomas (12) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
2
11
0
2
Order By: Relevance
“…These authors reported that the difference was probably due to the antibody used. FONSECA et al 5 also found low expression of Ki-67 in ACC. In our series, the expression of p53 and PCNA were higher in ACCs than in PA but lower than in MEC.…”
Section: Discussionmentioning
confidence: 83%
“…These authors reported that the difference was probably due to the antibody used. FONSECA et al 5 also found low expression of Ki-67 in ACC. In our series, the expression of p53 and PCNA were higher in ACCs than in PA but lower than in MEC.…”
Section: Discussionmentioning
confidence: 83%
“…In our study 11% and 16%, of muco epidermoid carcinoma and adenoid cystic carcinoma were respectively negative for this marker. In the study reported by Cleveland expression of Ki67 was observed in 88.2% of adenoid cystic carcinoma (Lazzaro and Cleveland, 2000) but Fonseka et al reported a low incidence of this marker in adenoid cystic carcinoma (Fonseca et al, 1997).…”
Section: Discussionmentioning
confidence: 93%
“…However, Fonseca et al. (34) observed lower number of mitoses in the cribriform and tubular patterns of cystic adenoid carcinoma, with higher values for the solid pattern. Similar results were also observed for the solid pattern of epithelial–myoepithelial carcinomas and polymorphous low grade adenocarcinomas.…”
Section: Discussionmentioning
confidence: 95%